Comparative study on the molecular chain orientation and strain-induced crystallization behaviors of HNBR with different acrylonitrile content under uniaxial stretching. (26th March 2021) - Zhang, Xi; Wu, Jing; Xu, Zhiqiang; Yue, Dongmei; Wu, Sizhu; Yan, Shouke; Lu, Yonglai; Zhang, Liqun
Abstract: Molecular chain orientation and strain-induced crystallization (SIC) behaviors of hydrogenated nitrile butadiene rubber (HNBR) with acrylonitrile content of 19%, 33%, 41%, 44%, i.e., HNBR-19 to HNBR-44, were characterized by using polarized FTIR spectroscopy and synchrotron radiation WAXD. Results demonstrated that the hydrogenated butadiene and acrylonitrile segments showed different orientation behaviors in these HNBRs. Orientation decreased with increasing acrylonitrile content, except for HNBR-44. HNBR-19 had the highest SIC ability and the crystals were composed of only hydrogenated butadiene homopolymer segments. HNBR-33 could not crystallize. As for HNBR-41 and HNBR-44 with high acrylonitrile content, HNBR-44 showed the better SIC ability and hydrogenated butadiene-acrylonitrile alternating copolymer segments were proved to participate in the crystallization. Relationship between microstructure and stress-strain characteristics was also discussed and results revealed that the relatively homogeneous crystal structure, higher crystal orientation and rapidly increasing molecular chain orientation were attributed to the highest stress value of HNBR-44 after SIC occurred. Graphical abstract: Image 1 Highlights: Acrylonitrile content determines the different molecular chain orientation of HNBR. HNBRs with different acrylonitrile content have various crystallization behaviors. Relationship between microstructure and stress-strain characteristics are discussed.